INFLUENCE OF ONLINE CUSTOMER RATINGS AND FEEDBACK ON RESTAURANT SALES THROUGH DELIVERY PLATFORMS IN BENGALURU - Pattanshetty, Sanjay; Murthy B. V, Srinivasa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The proliferation of online food delivery platforms such as Zomato and Swiggy has significantly transformed the restaurant industry in urban centres like Bengaluru. Customer-generated ratings and feedback on these platforms have become pivotal in shaping consumer choices and influencing restaurant performance. This study aims to explore the impact of online customer ratings and reviews on the sales of restaurants operating through these delivery platforms in Bengaluru. By examining the relationship between digital feedback and restaurant visibility, customer engagement, and overall business outcomes, the research seeks to provide insights into how online reputations affect sales in a competitive food service environment.